2006
DOI: 10.1002/acp.1323
|View full text |Cite
|
Sign up to set email alerts
|

Selective retrieval and induced forgetting in eyewitness memory

Abstract: This study analyses retrieval-induced forgetting (RIF) in eyewitness memory. Selective retrieval of specific information about an event could cause eyewitnesses to forget related contents. Based on a video of a man being robbed while withdrawing money from a cash machine, we examined the effects of partial retrieval on the most relevant aspects of the event: actions (Experiment 1) and offender characteristics (Experiment 2), in both immediate and long-term recall (24 hours). In both experiments long-term recal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
72
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 39 publications
4
72
0
Order By: Relevance
“…The results of Experiment 3 replicate the findings that a 24-h delay abolishes the retrieval-induced forgetting effect (Carroll et al, 2007;Mac Leod & Macrae, 2001;Saunders & Mac Leod, 2002) and that pre-delay and post-delay tests maintain the effect (Migueles & García-Bajos, 2007;Storm et al, 2006). These results suggest that methodological differences between studies on delay can explain some of the different findings across studies.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The results of Experiment 3 replicate the findings that a 24-h delay abolishes the retrieval-induced forgetting effect (Carroll et al, 2007;Mac Leod & Macrae, 2001;Saunders & Mac Leod, 2002) and that pre-delay and post-delay tests maintain the effect (Migueles & García-Bajos, 2007;Storm et al, 2006). These results suggest that methodological differences between studies on delay can explain some of the different findings across studies.…”
Section: Discussionsupporting
confidence: 73%
“…Studies by Carroll, Campbell-Ratcliffe, Murnane, and Perfect (2007), MacLeod and Macrae (2001), and Saunders and Mac Leod (2002) found that retrieval-induced forgetting dissipates when the retrieval practice and test phases are separated by 24 h. Salmon (2005, 2006) and Ford, Keating, and Patel (2004) found that retrieval-induced forgetting is present after 24 h, even though retrieval practice was spaced across several days. Further studies have found that significant retrieval-induced forgetting persists at 24-h (Migueles & García-Bajos, 2007) and 1-week delays (Storm et al, 2006); however, memory for all items was tested on two separate occasions: directly after retrieval practice and after a lengthy delay. Only one study (García-Bajos, Migueles, & Anderson, 2009) has used the same methodology as Mac Leod and Macrae's, and they found significant retrieval-induced forgetting after a 1-week delay (i.e., they tested memory only once, and all the retrieval practice tasks occurred on the same day).…”
Section: Experiments 3 Effects Of Delay On Mental Imagerymentioning
confidence: 99%
See 1 more Smart Citation
“…First, as described earlier, the impairment in recall performance for the tested participants relative to the nontested participants was only marginally significant. Second, our materials were highly coherent and interconnected in nature, and materials like these are highly resistant to retrieval-induced forgetting (Chan, 2009;Chan & LaPaglia, 2011;Migueles & Garcia-Bajos, 2007). Third, and perhaps most intriguingly, the decrement in performance for the tested participants might be the result of these participants noticing the inconsistencies between their memory of the video and the misinformation.…”
Section: Discussionmentioning
confidence: 99%
“…The dependency of RIF on interference suggests that RIF occurs as a response to interference, consistent with a role of inhibition in this phenomenon. Some investigators have also found that RIF dissipates after 24 hr (Baran, Wilson, & Spencer, 2010;Chan, 2009;MacLeod & Macrae, 2001;Saunders & MacLeod, 2002), although other studies have found RIF to be unaltered in magnitude after a day (Conroy & Salmon, 2005Ford, Keating, & Patel, 2004;Migueles & Garcia-Bajos, 2007) or even after a week (GarciaBajos et al, 2009;Migueles & Garcia-Bajos, 2007;Storm, Bjork, Bjork, & Nestojko, 2006;Tandoh & Naka, 2007). Most importantly, for present purposes, the amount of RIF depends on associations linking the memory target to its competitors: When the associates of a cue are connected to one another, retrieving some of them no longer impairs the recall of their competitors, a phenomenon known as an integration effect (Anderson & McCulloch, 1999).…”
mentioning
confidence: 99%